Effects of Incorporating Fine Aggregates and Polypropylene Microfibres on the Cracking Control of 3D Printed Cementitious Mixtures - Armando Vargas; Rafael Robayo-Salazar; Ruby Mejía de Gutiérrez (Buildings)
One of the most significant challenges for 3D printing of construction elements from cementitious materials is the control of cracking caused by various contraction–shrinkage mechanisms, such as drying, chemical, plastic and autogenous shrinkage. This study addresses the effects of incorporating fine aggregates (maximum size ≤ 1.18 mm), both natural and recycled, as well as short (6 mm long) polypropylene (PP) fibres on the control of cracking in cementitious mixtures based on Portland cement. Admixtures and/or mineral additions (modifiers), such as metakaolin, micro-silica, calcium carbonate, and fine powders obtained from construction and demolition wastes were used in the mixtures. Mini-slump, flow rate and buildability tests were used to characterize the mixtures in their fresh state. Extrudability was evaluated using laboratory-scale 3D printing tests conducted with a plunger–piston extrusion system. It was demonstrated that the physical characteristics of the aggregates directly influence the extrusion capacity. Mixtures containing natural aggregates exhibited greater fluidity and lower water demand than those containing recycled aggregates. The results indicated that the maximum allowable volume of fibres was 0.75%. To evaluate the cracking susceptibility of the mixtures, both with and without reinforcement, hollow beams composed of seven layers were printed, and subsequently the elements were exposed to the outdoor natural environment and inspected for a period of 90 days. The inclusion of the PP fibres effectively prevented the occurrence of fissures and/or cracks associated with shrinkage phenomena throughout the inspection period, unlike in unreinforced mixtures, which cracked after 14 days of exposure to the environment.